Problem-Based Learning Method to Improve Students' Critical Thinking Skills in Islamic Religious Education Learning at SD Negeri 24 Banda Aceh - Maisarah; Nazariah (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to analyze the effectiveness of the Problem-Based Learning (PBL) method in improving students' critical thinking skills in Islamic Religious Education (PAI) learning at SD Negeri 24 Banda Aceh. Critical thinking skills are essential competencies in 21st-century education, including in PAI learning which not only emphasizes cognitive aspects, but also understanding and applying religious values ​​in everyday life. The PBL method places students as the center of learning by presenting contextual problems that encourage exploration, analysis, and problem solving independently and collaboratively. This study used a quantitative approach with a quasi-experimental design. The research sample consisted of two groups of fifth-grade students, namely the experimental group using the PBL method and the control group using the conventional method. Data were collected through critical thinking tests, observations, and interviews. The results showed that students taught using the PBL method experienced a significant increase in critical thinking skills compared to the control group. In addition, this method also increases students' active participation, learning motivation, and conceptual understanding of PAI material. These findings indicate that the application of PBL in PAI learning can be an effective strategy to develop students' critical thinking skills from an early age. Therefore, teachers are advised to integrate PBL in learning planning to create a more meaningful and relevant learning experience for students.